ANALISIS SIFAT FISIK TANAH PADA BEBERAPA PENGGUNAAN LAHAN DI DESA MUNERANA KECAMATAN HEWOKLOANG KABUPATEN SIKKA - Yovita Yasintha Bolly; Henderikus Darwin Beja (Agrica: Journal of Sustainable Dryland Agriculture, 2022)
Soil's physical properties greatly affect the development and absorption of plant nutrients. This study aims to determine the physical properties of the soil on several land uses and slopes using the blepeng method. Soil collection was carried out from corn, nutmeg, cloves, and rainfed rice fields on two slope classes, namely 8-15% and 15-30%. Soil sampling used a diagonal system, where 9 sample points were taken from each location. The variables observed were bulk density, porosity, soil water content, soil texture and soil color. The results of the research show that the soil in Munerana Village, Hewokloang District, Sikka Regency is included in the texture of sandy loam soil, the low water content in the soil ranges from 14.87% to 25.50%, soil porosity is 25.66% to 29.12%, soil fill density is 1.17 me/100 g to 1.97 me/100 g and the soil color is dark reddish gray.